High-stability sodium ion battery positive electrode material as well as preparation method and application thereof
Through the co-doping method of cationic Ca2+ and multiple anions, the problem of limited improvement in the stability and cycle performance of the positive electrode material of sodium ion battery is solved, and the high stability and efficient electrochemical performance of sodium ion battery are achieved, especially in the long-term Significant improvement in cycle stability.
Patent Information
- Application Number
- CN202411718816.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2024-12-31
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, the performance of the positive electrode material of transition metal cation doped modified sodium ion battery is limited, and it is impossible to effectively improve the long cycle stability of sodium ion battery.
Using a strategy of co-doping of cation Ca2+ with multiple anions (such as F, Cl, N), the stability of the positive electrode material of sodium ion battery is improved by increasing the ion radius of Ca2+ and the electronegative of anions, forming a high-entropy composite material to maintain The stability of the original structure and improve electrochemical properties.
The high stability of the cathode material of sodium ion battery and the first Coulomb efficiency improvement have been achieved, extending the cycle life of the material and maintaining structural integrity.
Smart Images

Figure CN119230819A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of sodium ion battery materials, and specifically discloses a high-stability sodium ion battery positive electrode material and a preparation method and application thereof. Background Art
[0002] The vigorous development of new energy vehicles and the demand for power storage in large-scale energy storage equipment for renewable energy have accelerated the research and development of sodium-ion batteries. Similar to the development trend of lithium-ion batteries, the cathode materials of ternary sodium-ion batteries are developing in the direction of high specific energy and high power. However, the structural instability of pure-phase ternary sodium-ion battery cathode materials is prominent after continuous charge and discharge processes. It is urgent to find an effective protection method to achieve structural integrity and reversibility of electrochemical performance without sacrificing its own capacity.
[0003] In recent years, a lot of ion doping modifications have been carried out on the positive electrode materials of sodium ion batteries. For example, in the prior art, Mg 2+ The material obtained by doping Na 0.67 Ni 0.23 Mg 0.10 Mn 0.67 O 2 Compared with before doping, the stability can be improved; Cu 2+ Doping can inhibit material phase change and improve material cycle performance; K + As the pillar ion, the sodium vanadium phosphate material is doped and modified to reduce the volume change of the sodium vanadium phosphate material during the charge and discharge process. It can be seen that cation doping can improve the stability of the positive electrode material of the ternary sodium ion battery. For the modification of the positive electrode material of the sodium ion battery, most of them are doped with transition metal ions, and some anions are also doped. Although the material performance of the sodium ion battery is improved to a certain extent, the stability adjustment is too single, and the effect is not obvious, especially in the long-cycle stability of the sodium ion battery. There is still a lot of room for improvement. Based on this, the development of a material that can improve the performance of sodium ion batteries, especially the long-cycle stability, is of great significance to the development of sodium ion batteries. Summary of the invention
[0004] In view of the problem that the performance improvement of the sodium ion battery positive electrode material modified by transition metal cation doping in the prior art is limited and the long cycle stability of the sodium ion battery cannot be improved, the present invention provides a high-stability sodium ion battery positive electrode material. The present invention uses a strategy of co-doping with a cation and multiple anions to allow the doped ions to protect the structure of the sodium ion battery positive electrode material, so that it obtains high stability and improves the battery specific capacity and first coulomb efficiency of the sodium ion battery.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions.
[0006] The first aspect of the present invention provides a high-stability sodium ion battery positive electrode material, the chemical formula of the high-stability sodium ion battery positive electrode material is Na 1-2x Ca x Ni 0.6 Fe 0.3 Mn 0.15 F a Cl b N c O 2-(a+b+3c) / 2 , where 0<x<0.5, 0≤a≤0.1, 0≤b≤0.1, 0≤c≤0.2, and a, b and c cannot be 0 at the same time.
[0007] Compared with the prior art, the present invention adopts a variety of ion doping methods to obtain a high-stability sodium ion battery positive electrode material. 2+ It is doped with various non-metallic elements such as N, F, and Cl to improve the stability of sodium ion positive electrode materials. 2+ The ionic radius is larger than that of Na + The ionic radius of Ca 2+ After doping, Na + The position does not participate in the redox reaction and increases the interlayer spacing of the material to facilitate the rapid insertion / extraction of sodium ions. It can also form interlayer pillars through O-Ca-M (M represents Ni, Fe, Mn) bonds to strengthen the bonding between two adjacent MO 6 The links between the layers act to suppress phase changes, allowing the material to maintain its original crystal structure.
[0008] Furthermore, anion doping can increase the working voltage of the positive electrode material of sodium ion batteries through its strong electronegativity, and increase the oxygen vacancy concentration to increase the discharge capacity of the material and thus improve its first coulombic efficiency (ICE). At the same time, under the action of multiple anions, high entropy composite materials can be formed, which can make transition metals and non-metal elements in MO 6 The layer distribution is more uniform, which is more conducive to its local highly disordered state, which can almost ignore the slight changes in the local structure brought about by the redox reaction and maintain the original structure to the greatest extent.
[0009] In summary, the present invention doped with Ca 2+ And a variety of cations can have a dual protective effect on the overall structural stability of the sodium ion battery positive electrode material, making it reach a highly stable state, and thereby improving the capacity and first coulombic efficiency of the sodium ion battery positive electrode material.
[0010] Preferably, the high stability sodium ion battery positive electrode material is Na 0.88 Ca 0.06 Ni 0.6 Fe 0.3 Mn0.15 F 0.1 Cl 0. 1 N 0.04 O 1.93 、Na 0.2 Ca 0.4 Ni 0.6 Fe 0.3 Mn 0.15 F 0.08 Cl 0.06 N 0.12 O 1.75 、Na 0.88 Ca 0.06 Ni 0.6 Fe 0.3 Mn 0.15 Cl 0.1 N 0.0 4 O 1.89 、Na 0.88 Ca 0.06 Ni 0.6 Fe 0.3 Mn 0.15 F 0.1 N 0.04 O 1.89 Or Na 0.88 Ca 0.06 Ni 0.6 Fe 0.3 Mn 0.15 F 0.1 Cl 0.1 O 1.9 Any one of .
[0011] The second aspect of the present invention provides a method for preparing the high-stability sodium ion battery positive electrode material, comprising the following steps: Step 1, weighing a nickel source, an iron source, a manganese source, a sodium source, a calcium source, a fluorine source, a nitrogen source and a chlorine source, and ball milling to obtain a mixed powder; Step 2: heating the mixed powder to 800° C.-900° C. and sintering to obtain the high-stability sodium ion battery positive electrode material.
[0012] Preferably, in step 1, the nickel source is nickel sulfate.
[0013] Preferably, in step 1, the iron source is any one or both of iron oxide or iron sulfate.
[0014] Preferably, in step 1, the manganese source is any one or both of manganese dioxide and manganese sulfate.
[0015] Preferably, in step 1, the sodium source is any one or more of sodium hydroxide, sodium chloride or sodium sulfate.
[0016] Preferably, in step 1, the calcium source is any one or more of calcium carbonate, calcium chloride or calcium hydroxide.
[0017] Preferably, in step 1, the fluorine source is any one or both of sodium fluoride and calcium fluoride.
[0018] Preferably, in step 1, the nitrogen source is urea.
[0019] Preferably, in step 1, the chlorine source is any one or both of sodium chloride or calcium chloride.
[0020] Preferably, in step 1, the rotation speed of the ball mill is 350 rpm-500 rpm, and the time of the ball mill is 2 h-8 h.
[0021] Preferably, in step 2, the temperature is increased by programmed temperature increase, wherein the heating rate of the programmed temperature increase is 3°C / min-8°C / min.
[0022] Preferably, in step 2, the sintering time is 4h-20h.
[0023] The third aspect of the present invention provides an application of the high-stability sodium ion battery positive electrode material in a sodium ion battery.
[0024] In summary, the present invention provides a high-stability sodium ion battery positive electrode material and a preparation method thereof. The present invention utilizes a strategy of co-doping a cation and multiple anions so that the doped ions protect the structure of the sodium ion battery positive electrode material, thereby obtaining high stability and improving the battery specific capacity and first coulombic efficiency of the sodium ion battery. The high-stability sodium ion battery positive electrode material provided by the present invention effectively solves the problem that the performance improvement of the transition metal cation-doped modified sodium ion battery positive electrode material in the prior art is limited and the long-cycle stability of the sodium ion battery cannot be improved, providing a new idea for the design of sodium ion battery positive electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a cross-sectional electron microscope image of the sodium ion battery positive electrode material obtained in Example 1 before charging and discharging; Figure 2 This is a cross-sectional electron microscope image of the sodium ion battery positive electrode material obtained in Example 1 after charge and discharge; Figure 3 This is a cross-sectional electron microscope image of the sodium ion battery positive electrode material obtained in Comparative Example 1 before charging and discharging; Figure 4 This is a cross-sectional electron microscope image of the sodium ion battery positive electrode material obtained in Comparative Example 1 after charge and discharge. DETAILED DESCRIPTION
[0026] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Example 1 This embodiment provides a high-stability sodium ion battery positive electrode material Na 0.88 Ca 0.06 Ni 0.6 Fe 0.3 Mn 0.15 F 0. 1 Cl 0.1 N 0.04 O 1.93 , specifically including the following: Step 1: weigh 8.7 mmol of sodium hydroxide, 6 mmol of nickel sulfate hexahydrate, 1.5 mmol of iron oxide, 1.5 mmol of manganese dioxide, 0.55 mmol of calcium carbonate, 0.05 mmol of calcium chloride, 0.1 mmol of sodium fluoride, and 0.2 mmol of urea, mix well, and use a PM100 ball mill at 400 rpm for 4 hours to obtain a mixed powder; Step 2: In a muffle furnace, the mixed powder is heated to 850°C at a heating rate of 5°C / min, sintered for 16 hours, and then cooled to room temperature to obtain the high-stability sodium ion battery positive electrode material Na 0.88 Ca 0.06 Ni 0.6 Fe 0. 3 Mn 0.15 F 0.1 Cl 0.1 N 0.04 O 1.84 .
[0028] Example 2 This embodiment provides a high-stability sodium ion battery positive electrode material Na 0.2 Ca 0.4 Ni 0.6 Fe 0.3 Mn 0.15 F 0.08 Cl 0.06 N 0.12 O 1.75 , specifically including the following: Step 1: weigh 0.3 mmol of sodium sulfate, 6 mmol of nickel sulfate hexahydrate, 1.5 mmol of iron sulfate, 1.5 mmol of manganese sulfate, 4 mmol of calcium carbonate, 0.6 mmol of sodium chloride, 0.8 mmol of sodium fluoride, and 0.6 mmol of urea, mix them evenly, and use a PM100 ball mill at a speed of 350 rpm for 8 hours to obtain a mixed powder; Step 2: In a muffle furnace, the mixed powder is heated to 800°C at a heating rate of 4°C / min, sintered for 20 hours, and then cooled to room temperature to obtain the high-stability sodium ion battery positive electrode material Na 0.2 Ca 0.4 Ni 0.6 Fe 0.3 Mn 0.15 F 0.08 Cl 0.06 N 0.12 O 1.75 .
[0029] Example 3 This embodiment provides a high-stability sodium ion battery positive electrode material Na 0.88 Ca 0.06 Ni 0.6 Fe 0.3 Mn 0.15 Cl 0.1 N 0.04 O 1.89 , specifically including the following: Step 1: weigh 8.8 mmol of sodium hydroxide, 6 mmol of nickel sulfate hexahydrate, 1.5 mmol of iron oxide, 1.5 mmol of manganese dioxide, 0.55 mmol of calcium carbonate, 0.05 mmol of calcium chloride, and 0.2 mmol of urea, mix well, and use a PM100 ball mill at 400 rpm for 4 hours to obtain a mixed powder; Step 2: In a muffle furnace, the mixed powder is heated to 850°C at a heating rate of 5°C / min, sintered for 16 hours, and then cooled to room temperature to obtain the high-stability sodium ion battery positive electrode material Na 0.88 Ca 0.06 Ni 0.6 Fe 0. 3 Mn 0.15 Cl 0.1 N 0.04 O 1.89 .
[0030] Example 4 This embodiment provides a high-stability sodium ion battery positive electrode material Na 0.88 Ca 0.06 Ni0.6 Fe 0.3 Mn 0.15 F 0. 1 N 0.04 O 1.89 , specifically including the following: Step 1: weigh 8.7 mmol of sodium hydroxide, 6 mmol of nickel sulfate hexahydrate, 1.5 mmol of iron oxide, 1.5 mmol of manganese dioxide, 0.6 mmol of calcium carbonate, 0.1 mmol of sodium fluoride, and 0.2 mmol of urea, mix well, and use a PM100 ball mill at 400 rpm for 4 hours to obtain a mixed powder; Step 2: In a muffle furnace, the mixed powder is heated to 850°C at a heating rate of 5°C / min, sintered for 16 hours, and then cooled to room temperature to obtain the high-stability sodium ion battery positive electrode material Na 0.88 Ca 0.06 Ni 0.6 Fe 0. 3 Mn 0.15 F 0.1 N 0.04 O 1.89 .
[0031] Example 5 This embodiment provides a high-stability sodium ion battery positive electrode material Na 0.88 Ca 0.06 Ni 0.6 Fe 0.3 Mn 0.15 F 0. 1 Cl 0.1 O 1.9 , specifically including the following: Step 1, weigh 8.7 mmol of sodium hydroxide, 6 mmol of nickel sulfate hexahydrate, 1.5 mmol of iron oxide, 1.5 mmol of manganese dioxide, 0.55 mmol of calcium carbonate, 0.05 mmol of calcium chloride, and 0.1 mmol of sodium fluoride, mix well, and use a PM100 ball mill at 400 rpm for 4 hours to obtain a mixed powder; Step 2: In a muffle furnace, the mixed powder is heated to 850°C at a heating rate of 5°C / min, sintered for 16 hours, and then cooled to room temperature to obtain the high-stability sodium ion battery positive electrode material Na 0.88 Ca 0.06 Ni 0.6 Fe 0. 3 Mn 0.15 F 0.1 Cl0.1 O 1.9 .
[0032] Comparative Example 1 This comparative example provides a sodium ion battery positive electrode material NaNi 0.6 Fe 0.3 Mn 0.15 O 2 Compared with Example 1, there is no Ca, F, Cl and N doping, and other components and amounts remain the same, specifically including the following: Step 1: weigh 10 mmol of sodium hydroxide, 6 mmol of nickel sulfate hexahydrate, 1.5 mmol of iron oxide, and 1.5 mmol of manganese dioxide, mix them evenly, and use a PM100 ball mill at 400 rpm for 4 hours to obtain a mixed powder; Step 2: In a muffle furnace with air atmosphere, the mixed powder is heated to 850°C at a heating rate of 5°C / min, sintered for 16 hours, and then cooled to room temperature with the furnace to obtain the high-stability sodium ion battery positive electrode material NaNi 0.6 Fe 0.3 Mn 0.15 O 2 .
[0033] Comparative Example 2 This comparative example provides a sodium ion battery positive electrode material Na 0.88 Mg 0.06 Ni 0.6 Fe 0.3 Mn 0.15 F 0.1 Cl 0.1 N 0.0 4 O 1.84 Compared with Example 1, Ca is replaced with an equal molar amount of Mg, and other components and amounts remain the same, specifically including the following: Step 1: weigh 8.7 mmol of sodium hydroxide, 6 mmol of nickel sulfate hexahydrate, 1.5 mmol of iron oxide, 1.5 mmol of manganese dioxide, 0.55 mmol of magnesium carbonate, 0.05 mmol of magnesium chloride, 0.1 mmol of sodium fluoride, and 0.2 mmol of urea, mix well, and use a PM100 ball mill at 400 rpm for 4 hours to obtain a mixed powder; Step 2: In a muffle furnace, the mixed powder is heated to 850°C at a heating rate of 5°C / min, sintered for 16 hours, and then cooled to room temperature to obtain the high-stability sodium ion battery positive electrode material Na 0.88 Mg 0.06 Ni 0.6 Fe 0. 3Mn 0.15 F 0.1 Cl 0.1 N 0.04 O 1.84 .
[0034] Comparative Example 3 This comparative example provides a sodium ion battery positive electrode material Na 0.88 Ca 0.06 Ni 0.6 Fe 0.3 Mn 0.15 F 0.1 Cl 0.1 P 0.0 4 O 1.84 Compared with Example 1, N is replaced by an equimolar amount of P, and other components and amounts remain the same, specifically including the following: Step 1: weigh 8.7 mmol of sodium hydroxide, 6 mmol of nickel sulfate hexahydrate, 1.5 mmol of iron oxide, 1.5 mmol of manganese dioxide, 0.55 mmol of calcium carbonate, 0.05 mmol of calcium chloride, 0.1 mmol of sodium fluoride, and 0.2 mmol of phosphorus trioxide, mix well, and use a PM100 ball mill at 400 rpm for 4 hours to obtain a mixed powder; Step 2: In a muffle furnace, the mixed powder is heated to 850°C at a heating rate of 5°C / min, sintered for 16 hours, and then cooled to room temperature to obtain the high-stability sodium ion battery positive electrode material Na 0.88 Ca 0.06 Ni 0.6 Fe 0. 3 Mn 0.15 F 0.1 Cl 0.1 P 0.04 O 1.84 .
[0035] Comparative Example 4 This comparative example provides a sodium ion battery positive electrode material Na 0.88 Ca 0.06 Ni 0.6 Fe 0.3 Mn 0.15 I 0.1 Cl 0.1 N 0.0 4 O 1.84 Compared with Example 1, F is replaced by an equimolar amount of I, and other components and amounts remain the same, specifically including the following contents: Step 1: weigh 8.7 mmol of sodium hydroxide, 6 mmol of nickel sulfate hexahydrate, 1.5 mmol of iron oxide, 1.5 mmol of manganese dioxide, 0.55 mmol of calcium carbonate, 0.05 mmol of calcium chloride, 0.1 mmol of sodium iodide, and 0.1 mmol of urea, mix well, and use a PM100 ball mill at 400 rpm for 4 hours to obtain a mixed powder; Step 2: In a muffle furnace, the mixed powder is heated to 850°C at a heating rate of 5°C / min, sintered for 16 hours, and then cooled to room temperature to obtain the high-stability sodium ion battery positive electrode material Na 0.88 Ca 0.06 Ni 0.6 Fe 0. 3 Mn 0.15 I 0.1 Cl 0.1 N 0.04 O 1.84 .
[0036] In order to further demonstrate the technical effect of the present invention, the present invention conducted application tests on the sodium ion battery positive electrode materials obtained in Examples 1-5 and Comparative Examples 1-4, and the specific operations are shown in the test examples.
[0037] Test example S1. Evenly mix 0.08 g of the sodium ion battery positive electrode material, 0.01 g of acetylene black, 0.01 g of polyvinylidene fluoride and 2 mL of N-methylpyrrolidone to obtain a positive electrode slurry; S2, the positive electrode slurry is coated on aluminum foil to make a positive electrode sheet, and in an inert atmosphere, a metal sodium sheet is used as a negative electrode sheet, a Whatman glass microfiber is used as a separator, and 1 mol / L NaClO 4 The solution is an electrolyte solution, wherein the solvent is ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1, and a CR2025 button-type battery is assembled.
[0038] The present invention performs a constant current charge / discharge rate test on the button cell obtained in the test example. The constant current charge / discharge rate test is performed using a LAND test instrument. The charge and discharge voltage is 2.0V-4.2V. The test results are shown in Table 1.
[0039] Table 1 Electrochemical performance test results of sodium ion batteries prepared using various sodium ion battery cathode materials
[0040] It can be seen from the data in Table 1 that, compared with the performance data of Comparative Examples 1-4, the sodium ion battery positive electrode material provided by the embodiment of the present invention has high stability and higher total capacity and first coulombic efficiency.
[0041] The present invention also performs electron microscope scanning on the sodium ion battery positive electrode material obtained in Example 1 and the sodium ion battery positive electrode material obtained in Comparative Example 1 after charge and discharge, and the results are as follows: Figure 1-2 As shown. Figure 1 and Figure 2 By comparison, it can be seen that after charge and discharge, the cross section of the red frame area of the material in comparative example 1 is broken and fragmented, forming many uneven pits, which is in sharp contrast to before charge and discharge, while the cross section of the material in embodiment 1 after charge and discharge is still very smooth and not much different from before charge and discharge. 2+ With F - , Cl - and N 3- The morphology changes of doped modified materials after charging and discharging are greatly improved.
[0042] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A high-stability sodium ion battery positive electrode material, characterized in that: The chemical formula of the high-stability sodium ion battery positive electrode material is Na 1-2x Ca x Ni 0.6 Fe 0.3 Mn 0.15 F a Cl b N c O 2-(a+b+3c) / 2 , where 0<x<0.5, 0≤a≤0.1, 0≤b≤0.1, 0≤c≤0.2, and a, b and c cannot be 0 at the same time.
2. The high-stability sodium ion battery positive electrode material according to claim 1, characterized in that: The high-stability sodium ion battery positive electrode material is Na 0.88 Ca 0.06 Ni 0.6 Fe 0.3 Mn 0.15 F 0.1 Cl 0.1 N 0.04 O 1.93 、Na 0.2 Ca 0.4 Ni 0.6 Fe 0.3 Mn 0.1 5F 0.08 Cl 0.06 N 0.12 O 1.75 、Na 0.88 Ca 0.06 Ni 0.6 Fe 0.3 Mn 0.15 Cl 0.1 N 0.04 O 1.89 、Na 0.88 Ca 0.06 Ni 0.6 Fe 0.3 Mn 0.15 F 0. 1N 0.04 O 1.89 Or Na 0.88 Ca 0.06 Ni 0.6 Fe 0.3 Mn 0.15 F 0.1 Cl 0.1 O 1.9 Any one of .
3. A method for preparing a high-stability sodium ion battery positive electrode material according to claim 1 or 2, characterized in that: The steps include: Step 1, weighing a nickel source, an iron source, a manganese source, a sodium source, a calcium source, a fluorine source, a nitrogen source and a chlorine source, and ball milling to obtain a mixed powder; Step 2: heating the mixed powder to 800° C.-900° C. and sintering to obtain the high-stability sodium ion battery positive electrode material.
4. The method for preparing a high-stability sodium ion battery positive electrode material according to claim 3, characterized in that: In step 1, the nickel source is nickel sulfate; and / or In step 1, the iron source is any one or both of iron oxide and iron sulfate; and / or In step 1, the manganese source is any one or both of manganese dioxide and manganese sulfate.
5. The method for preparing a high-stability sodium ion battery positive electrode material according to claim 3, characterized in that: In step 1, the sodium source is any one or more of sodium hydroxide, sodium chloride or sodium sulfate; and / or In step 1, the calcium source is any one or more of calcium carbonate, calcium chloride or calcium hydroxide; and / or In step 1, the fluorine source is any one or both of sodium fluoride and calcium fluoride; and / or In step 1, the nitrogen source is urea; and / or In step 1, the chlorine source is any one or both of sodium chloride and calcium chloride.
6. The method for preparing a high-stability sodium ion battery positive electrode material according to claim 3, characterized in that: In step 1, the rotation speed of the ball mill is 350 rpm-500 rpm, and the time of the ball mill is 2 h-8 h.
7. The method for preparing a high-stability sodium ion battery positive electrode material according to claim 3, characterized in that: In step 2, the temperature is increased by programmed temperature increase, wherein the heating rate of the programmed temperature increase is 3°C / min-8°C / min.
8. The method for preparing a high-stability sodium ion battery positive electrode material according to claim 3, characterized in that: In step 2, the sintering time is 4h-20h.
9. Use of the high-stability sodium ion battery positive electrode material according to any one of claims 1 to 2 in a sodium ion battery.
Citation Information
Patent Citations
Multi-anion doped single crystal high-nickel positive electrode material and preparation method thereof
CN112652771A
Metal ion doped modified sodium ion material as well as preparation method and application thereof
CN114005969A
Fluorine and nitrogen co-doped sodium ion battery layered positive electrode material and preparation method and application thereof
CN115295793A
Anion-cation co-doped high-manganese layered oxide sodium ion battery positive electrode material and preparation method thereof
CN117525382A
Layered oxide positive electrode active material, and positive electrode plate containing same, sodium ion battery, and electrical apparatus
WO2023123049A1
